El paisaje cultural de la Parroquia Taquil del Cantón Loja, como referente para la elaboración de una propuesta artística contemporánea - Quevedo Torres, Jackeline Del Cisne (2022)
The present research of qualitative character in which the study of components, elements, characteristics, etc., of the cultural landscape from the artistic and aesthetic field is proposed to later focus on the study of the cultural landscape of the Taquil Parish of the Loja Canton. In the first instance, the historical and landscape context of the sector will be approached, then the investigation of theoretical aspects on landscape, cultural landscape and contemporary art, also important aspects of artists and works of Jean Pierre Weill and Anselm Kiefer will be considered as referents from which the most relevant technical and aesthetic characteristics will be analyzed to carry out the artistic proposal. Different methods will be used such as: bibliographic which will allow collecting information about the cultural landscape of the Taquil Parish, the landscape, cultural landscape and contemporary art through books, magazines, websites, etc., to elaborate the theoretical-aesthetic component; the deductive method will differentiate qualities on the techniques of data collection-visual or audio-visual information of the proposed topics, as well as it will also allow establishing criteria and artistic positioning that founds the process of recreation of the work. The experimental method subsequent to the work in situ will allow the abstraction of symbols and signs, as well as the integration and visibility of the natural landscape, and the application of various techniques and materials to consolidate the contemporary artistic proposal.